Effect of resistance training on osteopenic rat bones in neonatal streptozotocin-induced diabetes: Analysis of GLUT4 content and biochemical, biomechanical, densitometric, and microstructural evaluation - de Melo Yamamoto, Aline Pedro [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Astolphi, Rafael Dias [UNESP]; de Oliveira da Mota, Max Sander [UNESP]; Louzada, Mário Jefferson Quirino [UNESP]; de Lima Coutinho Mattera, Maria Sara [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Ervolino, Edilson [UNESP]; Tsosura, Thaís Verônica Saori [UNESP]; Belardi, Bianca Elvira [UNESP]; dos Santos, Rodrigo Martins [UNESP]; Okamoto, Maristela Mitiko; et al. (Elsevier, 2021)
Aims: To investigate the effect of resistance training-RT on glycemia, expression of the glucose transporter-GLUT4, bone mineral density-BMD, and microstructural and biomechanical properties of osteopenic rat bones in neonatal streptozotocin-induced diabetes. Main methods: Sixty-four 5-day-old male rats were divided into two groups: control and diabetic rats injected with vehicle or streptozotocin, respectively. After 55 days, densitometric analysis-DA of the tibia was performed. These groups were subdivided into four subgroups: non-osteopenic control-CN, osteopenic control-OC, non-osteopenic diabetic-DM, and osteopenic diabetic-OD. The OC and OD groups were suspended by their tails for 21 days to promote osteopenia in the hindlimb; subsequently, a second DA was performed. The rats were subdivided into eight subgroups: sedentary control-SC, sedentary osteopenic control-SOC, exercised control-EC, exercised osteopenic control-EOC, sedentary diabetic-SD, sedentary osteopenic diabetic-SOD, exercised diabetic-ED, and exercised osteopenic diabetic-EOD. For RT, the rats climbed a ladder with weights secured to their tails for 12 weeks. After RT, a third DA was performed, and blood samples, muscles, and tibias were assessed to measure glycemia, insulinemia, GLUT4 content, bone maximum strength, fracture energy, extrinsic stiffness, BMD, cancellous bone area, trabecular number, and trabecular width. Key findings: After RT, glycemia, GLUT4 content, BMD, and bone microstructural and biomechanical properties were improved in diabetic rats (osteopenic and non-osteopenic). However, RT had no effect on these parameters in the EC and SC groups. Significance: These results suggest that RT improves GLUT4 content, BMD, and microstructural and biomechanical properties of bone in osteopenic and non-osteopenic diabetic rats and is effective in controlling glycemia.
Keywords: Bone mineral density; Diabetes mellitus; GLUT4; Insulin sensitivity; Osteopenia; Resistance training